Structured computer organization - Tanenbaum, Andrew S.; Goodman, James R. (Upper Saddle River, New Jersey : Prentice-Hall, 1999)
This book takes a modern structured, layered approach to understanding computer systems. It's highly accessible - and it's been thoroughly updated to reflect today's most critical new technologies, including Pentium II and UltraSPARC microprocessors, Windows NT and Java Virtual Machines.Tanenbaum and Goodman present a computer as a series of layers, each one built upon the ones below it, and understandable as a separate entity. The book includes detailed coverage at the digital logic and micro-architecture levels, instruction set level, and operating system machine level, and contains a completely rewritten and updated chapter on parallel computer architecture. This new edition includes a wealth of new material about modern I/O devices, a detailed discussion of the Java Virtual Machine (including a microprogrammed implementation of a subset of a JVM), extensive coverage of multiprocessing, and much more.For all computer professionals and engineers who need an overview or introduction to computer architecture.
1. Introduction -- 2. Computer systems organization -- 3. The digital logic level -- 4. The microarchitecture level -- 5. The instruction set architecture level -- 6. The operating system machine level -- 7. The assembly language level -- 8. Parallel computer architectures -- 9. Reading list and bibliography -- A. Binary numbers -- B. Floating-point numbers -- C. Assembly language programming.
Includes bibliographical references (pages 613-629) and index.
Keywords: COMPUTER PROGRAMMING